Mental Health Day Hospitals and Lockdown Due to COVID-19 in Spain - Antonio José Sánchez-Guarnido; Valentina Lucena; Aurora Torrent; Laura Bosa; Virginia Martinez-López; Ana Cuartiles-Berenguer; Iolanda Batalla (Frontiers in Psychology, 2022)
IntroductionThe COVID-19 pandemic has forced changes in patient care in Mental Health Day Hospitals (MHDHs).ObjectivesTo study the interventions performed in MHDHs during the pandemic in comparison with those performed in other facilities and to analyze the new hospital admissions in both groups.MethodA retrospective multicenter cohort study comparing the interventions received by a group of 161 patients admitted in MHDHs during the lockdown period in Spain with the interventions of another group of 109 patients who were treated at other facilities during lockdown.ResultsMHDHs reduced their face-to-face interventions during lockdown just as much as other facilities but implemented telematic intervention methods to a greater extent. Patients attached to MHDHs during lockdown were admitted significantly less and presented fewer urgent consultations in the following 6 months.ConclusionThe use of telepsychiatry made it feasible to adapt MHDHs to periods of lockdown, being useful to improve the continuity of care during the pandemic. In addition, it was possible to maintain a reduction in hospital admissions in patients treated at MHDHs.